Digital rails for agriculture: The role of DPIs, DPGs, and digital initiatives in accelerating farmer-centric innovation and core principles or “sutras” for agri DPIs - The Agri Collaboratory (CGIAR System Organization, 2025)
Over the past thirty years, Indian agriculture has undergone a profound digital transformation—evolving from early ICT experiments in the 1990s to the emergence of data-driven and AI-enabled Digital Public Infrastructure (DPI). What began with rural telecentres and credit cards has evolved into an integrated digital framework empowering farmers through real-time information, financial inclusion, and access to national markets. Each phase—from the Kisan Credit Card and e-Choupal to AgriStack and Digital Public Infrastructure—has progressively bridged gaps in knowledge, access, and opportunity, shaping a more resilient and connected farming future.